The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.3390/ijms17050731
|View full text |Cite
|
Sign up to set email alerts
|

Key Developments in Ionic Liquid Crystals

Abstract: Ionic liquid crystals are materials that combine the classes of liquid crystals and ionic liquids. The first one is based on the multi-billion-dollar flat panel display industry, whilst the latter quickly developed in the past decades into a family of highly-tunable non-volatile solvents. The combination yields materials with a unique set of properties, but also with many challenges ahead. In this review, we provide an overview of the key concepts in ionic liquid crystals, particularly from a molecular perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 157 publications
0
40
0
Order By: Relevance
“…The attachment of two long alkyl chains in the 4-and 5-positions of imidazolium or thiazolium rings is unusual because it requires a different synthetic approach than simply alkylating commercially available precursors, such as 1-methylimidazole, imidazole, or thiazole. While 1,3-dimethyl-4,5-bis(n-heptyl)imidazolium iodide (1-7) is non-mesomorphic, 1,3-dimethyl-4,5-bis(n-undecyl)imidazolium iodide (1-11), 1,3-dimethyl-4,5bis(n-pentadecyl)imidazolium iodide (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and the analogue with an additional methyl group in the 2-position (2) were found to be liquid-crystalline; they adopt SmA phases upon heating albeit over relatively narrow temperature ranges. For comparison, 3-methyl-4,5-bis(n-pentadecyl)thiazolium iodide (3) or 2-amino-4,5-bis(n-pentadecyl)imidazolium chloride (4) did not display liquid-crystalline properties under the conditions explored.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The attachment of two long alkyl chains in the 4-and 5-positions of imidazolium or thiazolium rings is unusual because it requires a different synthetic approach than simply alkylating commercially available precursors, such as 1-methylimidazole, imidazole, or thiazole. While 1,3-dimethyl-4,5-bis(n-heptyl)imidazolium iodide (1-7) is non-mesomorphic, 1,3-dimethyl-4,5-bis(n-undecyl)imidazolium iodide (1-11), 1,3-dimethyl-4,5bis(n-pentadecyl)imidazolium iodide (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and the analogue with an additional methyl group in the 2-position (2) were found to be liquid-crystalline; they adopt SmA phases upon heating albeit over relatively narrow temperature ranges. For comparison, 3-methyl-4,5-bis(n-pentadecyl)thiazolium iodide (3) or 2-amino-4,5-bis(n-pentadecyl)imidazolium chloride (4) did not display liquid-crystalline properties under the conditions explored.…”
Section: Discussionmentioning
confidence: 99%
“…Examination by POM revealed that the sample became plastic after the first transition upon heating. 7 Peak temperature. 8 The transition to the LC mesophase upon heating was preceded by multiple transitions ( Figure S4).…”
Section: -11mentioning
confidence: 99%
See 3 more Smart Citations